2020
DOI: 10.1111/gbi.12388
|View full text |Cite
|
Sign up to set email alerts
|

Associations between redox‐sensitive trace metals and microbial communities in a Proterozoic ocean analogue

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(242 reference statements)
0
2
1
Order By: Relevance
“…These observations differ from Sforna et al (2017) who suggested biologically controlled accumulation of TE in organic-rich globules in modern microbialites was a consequence of specific metabolic pathways (Sforna et al, 2017). By contrast, our results are similar to Rico et al (2020) who observed that living microbial mats from the Middle Island Sinkhole (located 23 m below the water level of Lake Huron) do not significantly influence bulk TE geochemistry at the sediment-water interface, although highly heterogeneous redox conditions were observed. Considering that the water column redox conditions (e.g., oxygen, sulfate, and iron concentrations) in the Middle Island Sinkhole could be analogous to those that were in Proterozoic shallow-marine environments (cf.…”
Section: Te Geochemistry: a Biosignature Of Benthic Microbial Activity?contrasting
confidence: 85%
“…These observations differ from Sforna et al (2017) who suggested biologically controlled accumulation of TE in organic-rich globules in modern microbialites was a consequence of specific metabolic pathways (Sforna et al, 2017). By contrast, our results are similar to Rico et al (2020) who observed that living microbial mats from the Middle Island Sinkhole (located 23 m below the water level of Lake Huron) do not significantly influence bulk TE geochemistry at the sediment-water interface, although highly heterogeneous redox conditions were observed. Considering that the water column redox conditions (e.g., oxygen, sulfate, and iron concentrations) in the Middle Island Sinkhole could be analogous to those that were in Proterozoic shallow-marine environments (cf.…”
Section: Te Geochemistry: a Biosignature Of Benthic Microbial Activity?contrasting
confidence: 85%
“…Sediment underlying the ~2 mm‐thick microbial mats is different than the surrounding Lake Huron sediment (Nold et al, 2013; Rico & Sheldon, 2019; Rico et al, 2020). Carbon isotope signatures in the sedimentary organic matter underlying the mats indicate that it is sourced from settling phytoplankton (Nold et al, 2013; Rico & Sheldon, 2019; Rico et al, 2020), and some trace metals such as molybdenum show modest enrichments due to particulate shuttling (Rico et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Sediment underlying the ~2 mm‐thick microbial mats is different than the surrounding Lake Huron sediment (Nold et al, 2013; Rico & Sheldon, 2019; Rico et al, 2020). Carbon isotope signatures in the sedimentary organic matter underlying the mats indicate that it is sourced from settling phytoplankton (Nold et al, 2013; Rico & Sheldon, 2019; Rico et al, 2020), and some trace metals such as molybdenum show modest enrichments due to particulate shuttling (Rico et al, 2019). Overall, the MIS sediments have higher total organic carbon, iron, and trace metal concentrations than Lake Huron sediments due to differences in redox chemistry and geomicrobiological conditions between the sinkhole and surrounding environment (Nold et al, 2013; Rico & Sheldon, 2019; Rico et al, 2019, 2020).…”
Section: Methodsmentioning
confidence: 99%